Acute Rheumatic Activity in a 49 year old Nepalese adult with established Rheumatic heart Disease: a case report - Hirachan, Anish; Manandhar, Reeju; Roka, Madhu; Sharma, Deewakar (Nepalese Heart Journal, 2016)
Rheumatic fever presenting late in adult beyond 25 years of age is a rare but common phenomena and noted in various case reports .The diagnosis of rheumatic activity is based on the same modified Jones criteria for rheumatic fever and rheumatic heart disease. Here we describe a 49 year old male , known rheumatic heart disease with severe aortic regurgitation and post aortic valve replacement who presented with fever and migratory polyarthritis along with history of preceding sore throat 2 weeks prior to this illness . He was managed with high dose of aspirin therapy along with oral penicillin after which he had dramatic improvement in his symptomatology and was discharged with good recovery. Nepalese Heart Journal 2016; 13(2): 39-40